2021
DOI: 10.1186/s12905-021-01262-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of the CHARISMA counseling intervention to support women’s use of pre-exposure prophylaxis: results of a pilot study

Abstract: Background Women may need or seek male partner approval to safely and consistently use oral antiretroviral pre-exposure prophylaxis (PrEP) or vaginal microbicides. We developed CHARISMA, a counseling intervention to support women’s relationships and their ability to consistently use HIV prevention products. Methods In a pilot study with 95 female participants in Johannesburg, South Africa, lay counselors implemented CHARISMA, assessing participants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Similarly, the recent Community Health Clinic Model for Agency in Relationships and Safer Microbicide Adherence (CHARISMA) found high acceptability and feasibility for a tailored lay counselor PrEP intervention aimed at building agency and safety in women's relationships. 28,29 Women also readily described the challenges posed by male partners and the complexities of disclosing, or even initiating, discussion of PrEP use within a relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the recent Community Health Clinic Model for Agency in Relationships and Safer Microbicide Adherence (CHARISMA) found high acceptability and feasibility for a tailored lay counselor PrEP intervention aimed at building agency and safety in women's relationships. 28,29 Women also readily described the challenges posed by male partners and the complexities of disclosing, or even initiating, discussion of PrEP use within a relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two process assessment surveys were conducted after SOP implementation, one each with site staff and leadership, to evaluate the SOP implementation process. Thirteen of the 14 HOPE sites implemented the SOP; the last site was participating in a separate study of an integrated PrEP and IPV counseling intervention called the Community Health clinic model for Agency in Relationships and Safer Microbicide Adherence (CHARISMA), following separate study-specific procedures and SOPs (22,23). The CHARISMA site was included in the needs assessment but did not complete the process evaluation.…”
Section: Sop Design and Implementationmentioning
confidence: 99%
“…TV scales from the tool prior to implementing the effectiveness study. However, interim evaluation of the pilot [31] suggested that the progress of constructs and items in the HEART evoked deeper, yet non-threatening reflection among participants of their relationship with a primary partner. This led us to revise and further study HEART constructs in the upcoming effectiveness study, rather than eliminate immediately.…”
Section: Plos Onementioning
confidence: 99%
“…From a feasibility perspective, a smaller tool with fewer items would take less time to implement in a busy clinic setting. In an interim assessment of CHARISMA acceptability and feasibility, most participants (61%) felt the tool took the right amount of time, while 25% felt it was too long [31]. On the other hand, some lay counselors noted that the flow of the tool, which moves from more normative items related to gender-based values to partner support, partner abuse and control, resistance towards HIV prevention and finally HIV prevention readiness facilitated participants' ability to think carefully about their current relationship.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation